Bone regeneration on chronic apical abscess after root canal treatment on left mandibular first molar: A case report - Diana Puspa Indah; Eko Fibryanto; le Elline Istanto (Wolters Kluwer Medknow Publications, 2019)
Background: A chronic apical abscess is defined as an inflammatory response to pulp infection and necrosis. It is identified by a step-wise onset, almost no discomfort, and the discontinuous release of pus through a related sinus tract. Radiographically, there are regular indications of bone destruction, such as radiolucency. The source of the infection in the root canal should be eradicated by root canal treatment. The main purpose of endodontic treatment is the finished debridement of the pulp tissue from the canal combined with the shaping and sufficient obstruction of the root canal system. This case report was written to show the proper management of a tooth with a chronic apical abscess and to reveal self-bone regeneration after treatment. Case Report: A 27-year-old woman complained of a cavity on her left lower back tooth, and she wanted it to be filled. There was a history of a fistula that appeared frequently in the gums near the decayed tooth. The radiographic examination showed that the caries had reached the pulp, along with a periapical lesion and bone destruction. The canals were prepared using a file instrument and irrigation with 5.25% sodium hypochlorite, 17% ethylenediaminetetraacetic acid, and 2% chlorhexidine gluconate. Calcium hydroxide paste was used as an intracanal medicament, and the canals were obturated using a continuous wave compaction technique. At the 4-month follow-up, healing of the periapical lesion and bone regeneration was evident. Conclusion: Adequate root canal treatment can result in the healing of periapical lesions and bone regeneration in chronic apical abscesses.